"FEATURES OF PROFESSIONAL DEFORMATION AND INNOVATIVE-ACMEOLOGICAL MODELS OF PROVIDING MENTAL HEALTH IN PRIMARY TEACHERS IN THE CONDITIONS OF GLOBALIZATION." (Universal International Scientific Journal, 2026)
This article analyzes the characteristics of professional deformation that may occur in primary school teachers in the context of globalization and the problems of ensuring their mental health. The study examines factors such as psychological stress, emotional exhaustion, stereotyped thinking, and decreased professional motivation that arise during the professional activities of teachers, especially in the period of maturity. It also scientifically substantiates the impact of the globalization process on the education system, new requirements for the pedagogical personality, and the need to maintain the psychological stability of the teacher in this process. The article highlights the theoretical foundations and practical significance of innovative acmeological approaches aimed at strengthening the mental health of primary school teachers, models supporting professional development. According to the results of the study, the use of the acmeological development model, psychological training, reflexive activity, and innovative pedagogical technologies is of great importance in preventing professional deformation in teachers, ensuring their psychological well-being, and developing professional maturity.
Keywords: : globalization, primary school teacher, professional deformation, mental health, innovative-acmeological model, professional development, maturity period, pedagogical activity, emotional exhaustion, psychological stability, reflection, pedagogical personality